HEALTH AND ENVIRONMENTAL CONCERNS OF ANTISCALANT APPLICATION IN WATER PURIFIERS - Vickneswari M; Monish Raj R; Vijaya Krishanan; Palthangam Ganesan; Jeevitha (The Bioscan, 2025)
The widespread use of antiscalants in water purifiers has become essential for preventing scale formation and enhancing the operational efficiency of membrane-based and thermal water treatment systems. However, the long-term implications of antiscalant use on human health and the environment are emerging as significant concerns. This review critically examines the chemical composition of commonly used antiscalants, their degradation products, and potential toxicity. Continuous exposure to residual antiscalants in drinking water may pose health risks, including gastrointestinal disturbances, renal stress, and bioaccumulation of certain heavy metals